1998
DOI: 10.1007/bf02375957
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and structural comparison of zinc-cobalt doped spinels with other doped lithium manganese spinels

Abstract: Abstract. Doping of lithium manganese spinels by zinc and cobalt of the type (LilxZnx)(Mn2-2x Co2x)O4 may stabilize the delithiated spinels and may offer some indications with respect to the validity of capacity fade models. There are structural chemical arguments for this cation distribution. These and other doped lithium manganese spinels were prepared by heat treatment (in the range between 500 and 800 ~ for 12 h) of solution precipitated precursors. Samples were characterised structurally and electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Considering the above-mentioned TM cation occupancy at Li tetrahedral sites at the shell (Figure b–d), the in situ formed structure at the surface of the Zn-doped samples should be spinel ZnMn 2 O 4 with some Zn atoms occupying Li sites and other Zn 2+ ions diffused into 16d Mn sites in bulk to form the LiZn x Mn 2– x O 4 phase, forming core–shell LiZn x Mn 2– x O 4 @ZnMn 2 O 4 . It is reported that the ionic radius of Zn 2+ in the tetrahedral coordination in the oxide spinel (0.60 Å) is quite similar to that of Li (0.59 Å), which further supports the feasibility of the Zn 2+ ion occupancy at tetrahedral Li sites to form the ZnMn 2 O 4 phase at the surface region.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Considering the above-mentioned TM cation occupancy at Li tetrahedral sites at the shell (Figure b–d), the in situ formed structure at the surface of the Zn-doped samples should be spinel ZnMn 2 O 4 with some Zn atoms occupying Li sites and other Zn 2+ ions diffused into 16d Mn sites in bulk to form the LiZn x Mn 2– x O 4 phase, forming core–shell LiZn x Mn 2– x O 4 @ZnMn 2 O 4 . It is reported that the ionic radius of Zn 2+ in the tetrahedral coordination in the oxide spinel (0.60 Å) is quite similar to that of Li (0.59 Å), which further supports the feasibility of the Zn 2+ ion occupancy at tetrahedral Li sites to form the ZnMn 2 O 4 phase at the surface region.…”
Section: Resultsmentioning
confidence: 55%
“…In contrast, the gradients of O and Mn intensities increase from the surface to the center region. Considering the above-mentioned TM cation occupancy at Li tetrahedral sites at the shell (Figure It is reported that the ionic radius of Zn 2+ in the tetrahedral coordination in the oxide spinel (0.60 Å) is quite similar to that of Li (0.59 Å), 32 which further supports the feasibility of the Zn 2+ ion occupancy at tetrahedral Li sites to form the ZnMn 2 O 4 phase at the surface region.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation